Genetic gain of soybean in the Paraná state, Brazil, in the period of 1985/86 through 1989/90, obtained by breeding - Alliprandini, Luís Fernando; Toledo, José Francisco Ferraz; Junior, Nelson S. Fonseca; Kiihl, Romeu Afonso de Souza; de Almeida, Leones Alves (Pesquisa Agropecuaria Brasileira, 1993)
The efficiency of the soybean breeding programs of Paraná, Brazil, was evaluated using data available from yield trials incorporated in the routine of the program. Data from the soybean official trials of 1985/96 to 1989/90, of three maturity groups, were used. The annual genetic gain in the Parana State from 1985/86 to 89/90 was 0.89% for the early, 0.38% for the semi-early, and -0.28% for the medium maturity group. These values, although significant to improve the State's productivity, were smaller than those obtained for the five previous years.